Characterizing the hypomethylated DNA methylation profile of nucleated red blood cells from cord blood. (November 2016) - de Goede, Olivia M; Lavoie, Pascal M; Robinson, Wendy P
Aim: To provide insight into fetal nucleated red blood cell (nRBC) development using genome-wide DNA methylation (DNAm) profiling.Materials & methods: The DNAm profile (Illumina 450K array) of cord blood (n = 7) derived nRBCs was compared with B cells, CD4 and CD8 T cells, natural killer cells, granulocytes, monocytes and placenta (n = 5).Results: nRBCs and placenta had similarly low array-wide DNAm compared with white blood cells, but their patterns of hypomethylation differed at biologically relevant subsets of the array. High interindividual variability in nRBC DNAm was driven by a negative association between DNAm and nRBC count.Conclusion: nRBC hypomethylation is likely an epigenetic signature of erythropoiesis rather than of early development. Variability in nRBC DNAm may stem from differences in the cell population's maturity or hematopoietic source.